Critical Geochemical and Microbial Reactions in Underground Hydrogen Storage: Quantifying Hydrogen Loss and Evaluating CO2 as Cushion Gas - Rana Al Homoud; Marcos Vitor Barbosa Machado; Hugh Daigle; Harun Ates (Hydrogen)
Hydrogen is a pivotal energy carrier for achieving sustainability and stability, but safe and efficient geological underground hydrogen storage (UHS) is critical for its large-scale application. This study investigates the impacts of geochemical and biochemical reactions on UHS, addressing challenges that threaten storage efficiency and safety. Geochemical reactions in saline aquifers, particularly the generation of hydrogen sulfide (H2S), were analyzed using advanced compositional and geochemical modeling calibrated with experimental kinetic data. The results indicate that geochemical reactions have a minimal effect on hydrogen consumption. However, by year 10 of storage operations, H2S levels could reach 12–13 ppm, necessitating desulfurization to maintain storage performance and safety. The study also examines the methanogenesis reaction, where microorganisms consume hydrogen and carbon dioxide to produce methane. Numerical simulations reveal that microbial activity under suitable conditions can reduce in situ hydrogen volume by up to 50%, presenting a critical hurdle to UHS feasibility. These findings highlight the necessity of conducting microbial analyses of reservoir brines during the screening phase to mitigate hydrogen losses. The novelty of this work lies in its comprehensive field-scale analysis of impurity-induced geochemical and microbial reactions and their implications for underground hydrogen storage. By integrating kinetic parameters derived from experimental data with advanced computational modeling, this study uncovers the mechanisms driving these reactions and highlights their impact on storage efficiency, and safety. By offering a detailed field-scale perspective, the findings provide a pivotal framework for advancing future hydrogen storage projects and ensuring their practical viability.